Integrating Project-Based Learning in English Language Teacher Education for Sustainable Development Goals (SDGs) - Yusupova, Mukhabbat; Gazieva, Saida; Abdullayeva, Zarinaxon; Umarova, Ziyoda; Akhmedova, Muyassar; Kambarova, Mukhayyo (International Journal of Language Education, 2025)
This study aimed to improve teacher education by integrating project-based learning (PBL) into English language instruction. A motivational-cognitive-reflective model was developed and implemented using a mixed-methods approach. Data were collected through surveys, interviews, and observations involving pre-service English teachers and faculty. The findings showed enhanced planning, collaboration, and instructional competencies. This improvement occurred because PBL fosters active engagement, critical thinking, and reflective learning aligned with authentic classroom contexts. The framework enabled students to apply theoretical knowledge to practical scenarios, aligning with CEFR and IELTS teaching standards. By promoting learner autonomy and contextual learning, the study advances Sustainable Development Goal 4 (Quality Education). The proposed model offers a scalable, evidence-based strategy for enhancing language teacher education globally.